A methodology to determine suitable placement of solar photovoltaic sources in the transmission system taking into account Voltage Stability Index (VSI) - Sie A.W.H.; Abidin I.Z.; Hashim H. (Institute of Electrical and Electronics Engineers Inc., 2023)
The integration of solar PVs which is projected to increase over the years creates concerns over stability. Reverse power flow occurs due to high PV penetration into the power system network. PV placement at proper locations in a transmission system is essential to maintain voltage stability. Improper placement will caused voltage stability of the system to be affected. However, if the PVs are connected at a strategic location it will lead to a more stable system. This paper presents a methodology for PV source placement in the transmission system while maintaining the stability of the. Voltage Stability Index (VSI) will be used as an indicator to measure the stability status of the system. Two test systems will be used for simulation for this research, the IEEE 30 Bus and 57 Bus Test System. The simulation results showed that proper placement of the PV source in the transmission system will lead to better stability to the system. © 2014 IEEE.